Advanced intorduction to digital society - Castells, Manuel (Cheltenham Edward Elgar Publishing, 2024)
This essential book documents the current configuration of digital society worldwide and examines its social, economic, political and cultural consequences. Presenting state-of-the-art empirical analysis and academic research, preeminent author Manuel Castells explores the profound impact that technology and digital transformation continues to have on the world as we know it.
Keywords: Digital sociological aspects; Social media; Network society